Nutrient Deficiencies in Production of Annual Floral Crops - James L. Gibson; Beth Bolles; Sheila Dunning; Theresa Friday; Dan Mullins; Carrie Stevenson; Larry Williams (EDIS)
ENH-1068, an 8-page illustrated fact sheet by James L. Gibson, Beth Bolles, Sheila Dunning, Theresa Friday, Dan Mullins, Carrie Stevenson, and Larry Williams, describes practices for nutrition monitoring and management for growers of annual floral crops. It describes essential nutrients and their translocation, provides a table of essential nutrients, and several figures showing symptoms of nutrient deficiencies. Includes a list of additional resources. Published by the UF Department of Environmental Horticulture, April 2007.